Review Paper on Six-Sigma Technique - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Six Sigma techniques have proven to be very successful in maintaining high profitability by product up-gradation and continuous improvement for all company organizations. The rate of growth of fair-size companies and organizations is directly linked to the Six-Sigma methods implementation. Six-Sigma is a term originally introduced around 1985. Six-sigma is a theory, a metric and a process that brings business perspective and opportunities to achieve great performance levels in both products and services. Comprehending the key characteristics, barriers, aspects and weak points of six sigma methods will enable organizations to promote their tactical directions and increase the need for supervision and training. That also generates appropriate possibilities for six sigma projects to be implemented. The main focus in six-sigma is on enhancing capacity and reducing waste. This paper describes in detail the definition of six-sigma. The paper also focuses on the six-sigma methodology along with factors needed to successfully incorporate six sigma methodologies.